Pumice and perlite co-substituted hydroxyapatite: fabrication and characterization - Serap (güngör) Koc (MANAS: Journal of Engineering)
The purpose of this study was to combine hydroxyapatite (HA) with pumice and perlite. A precipitation procedure was applied for synthesizing pure and doped hydroxyapatite. Samples were sintered at 1100°C for 1 h. These doped structures are characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM-EDS) and X-ray Fluorescence. Higher SiO2 and Al2O3 content was shown by XRF analysis. The XRD results revealed the existence of the HA, β-TCP and Ca5(PO4)2SiO4 phases. SEM images confirmed the sintering temperature and number of dopants had significant effect on grain sizes of the samples.